Pengaruh karakteristik pekerjaan dan kompetensi terhadap kinerja melalui komitmen organisasional - Purwanto, Bambang Heri; Soliha, Euis (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
The purpose of this study was to determine and analyze the relationship between job characteristics, competencies and organizational commitment to employee performance Pekalongan District Health Office. The population for this study is Pekalongan District Health Bureau staff totaling 104 people. Samples were taken by using census method. The research instrument was a questionnaire. The collected data was then processed using the technique of multiple regression analysis with SPSS (Statistical Package for Social Science). The analysis showed 1) the characteristics of the job does not affect the organizational commitment, 2) competence and significant positive effect on organizational commitment, 3) job characteristics and significant positive effect on performance, 4) the competence of positive and significant impact on performance, 5) organizational commitment is not berpengaruhi the performance